PENGENDALIAN PERANGKAT ELEKTRONIK BERBASIS MIKROKONTROLLER DENGAN ANDROID - Fanni Sukma; Dwiny Meidelfi; Ronal Hadi; Heru Samudera (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
The very rapid development of technology and the high level of human innovation have made the emergence of increasingly sophisticated technological products, one of which is the MCU node, a microcontroller system that has been integrated with various electronic modules and by using the C++ programming language, the automatic smart home control system, is one of the technological advances in the field of mechanics and electronics, both digital and analog, by integrating a smartphone as a remote to turn on and turn off certain electrical equipment using the MCU node as the main control and a link between smartphones. Remote application smart home as a media user interface for giving commands via the smartphone which will be executed by the MCU node and then the relay which will execute the electrical equipment installed at home